Analysis of Clinical Characteristics and Polysomnography Indicators of Obstructive Sleep Apnea–Hypopnea Syndrome Patients Based on Sleep Perception Types - Liu, Yishu; Tan, Huiwen; Yu, Yue; Zeng, Yin; Xiao, Li (Frontiers in Neurology, 2020)
Purpose: To explore the clinical characteristics of different sleep perception types of obstructive sleep apnea-hypopnea syndrome (OSAHS) patients, and analyse the correlation between sleep perception and polysomnography indicators in OSAHS patients. Methods: We retrospectively analysed 355 patients diagnosed with OSAHS by polysomnography at the Sleep Medicine Center of Shengjing Hospital of China Medical University. Patients saw a doctor due to snoring and daytime sleepiness from March 2017 to March 2018.We excluded the patients who are less than 18 years old, had a history of OSAHS treatment, had other sleep and psychiatric disorders and could not provide complete data. According to the patients’ explanation, medical history, polysomnography indicators and morning questionnaire after polysomnography, the patients were divided into normal sleep perception (NSP), positive sleep perception abnormal (PSPA) and negative sleep perception abnormal (NSPA). We analyze the demographic characteristics and polysomnography of the three groups with ANOVA and nonparametric tests. In addition, we conducted correlation analysis between sleep perception and polysomnography indicators. Results: 55.5% of OSAHS patients had sleep perception abnormalities, of which 35.5% were positive-perception abnormalities and 20% were negative-perception abnormalities. From the analysis of polysomnography indicators, the sleep perception abnormality was related to the frequency of spontaneous arousal of the patient(P=0.003), and was not related to the slight arousal caused by respiratory events, oxygen desaturations and limb movement events. OSAHS patients with PSPA had a higher oxygen desaturation index(P=0.046), but no significant difference in post hoc test. PSPA group had significantly lower REM latency, sleep efficiency and more WASO compared to the other sleep perception groups. Multivariate linear regression analyses after adjusting for age and sex revealed that sleep perception was related to LSaO2, TS90%, sleep efficiency and WASO. Conclusion: Sleep perception abnormality is common in OSAHS patients. OSAHS patients with different sleep perception types have different PSG profiles. The OSAHS patients with PSPA have more severe hypoxia levels at night that require timely personalized treatment.